Neoadjuvant Chemoradiotherapy for Stage III Non-Small Cell Lung Cancer - Sher, David J. (Frontiers in Oncology, 2017)
The local management of stage III non-small cell lung cancer is controversial. Although definitive chemoradiotherapy is considered a standard-of-care in the curative management of the disease, inadequate local control outcomes have led to various treatment strategies that incorporate surgical resection. Surgery alone has long been recognized as insufficient for this stage, and thus neoadjuvant strategies have been developed to treat micrometastatic disease and increase the probability of a complete resection. The optimal induction strategy has not yet been defined, however, with arguments favoring either preoperative chemotherapy or chemoradiotherapy. In this article, I will review the data supporting the use of neoadjuvant chemoradiotherapy and the randomized literature comparing the two approaches. The article will conclude with summary comparisons of these induction paradigms.